WATER HYACINTH (EICHHORNIA CRASSIPES) MODIFIED CITRIC ACID AS A METAL ADSORBENT IN LABORATORY LIQUID WASTE - Rifatul Mahmudah; Qumil Lailatu Nabilah; Wida Nuri Ahdiyati (Jurnal Neutrino: Jurnal Fisika dan Aplikasinya)
The cellulose content in water hyacinth (Eichhornia crassipes) shows potential as an adsorbent medium in the management of heavy metal waste generated from laboratory activities. Water hyacinth (Eichhornia crassipes) contains 60% cellulose which is rich in hydroxyl groups so that it can interact with metal ion adsorbate components. Water hyacinth adsorbent was modified using citric acid and its functional groups (carboxyl, hydroxyl, and lactone) were analyzed using Boehm titration. The modified adsorbent was applied to laboratory waste and the levels of copper (Cu), Chromium (Cr) and Cadmium (Cd) were analyzed using Atomic Absorption Spectrophotometry. Water hyacinth adsorbent was characterized using a Fourier Transform Infrared spectrometer to determine the active groups in the adsorbent. The FTIR results of the modified adsorbent showed that there was an absorption peak of the C=O ester group at wave numbers 1733-1734 cm-1 indicating an esterification reaction between cellulose and citric acid. Adsorption of chromium and cadmium metals had the highest percentage reduction at a dose of 2 grams of 98% and 37.40%, while for copper metal at a dose of 1.5 grams of adsorbent was 63.34%.